Brazil's Diplomacy Strategy in Responding to International Pressure on The Problem of Deforestation - Seniwati, Seniwati; Ranti, Munif Arif (Hasanuddin Journal of International Affairs, 2024)
This research analyzes Brazil's diplomatic strategy for overcoming the problem of deforestation in the Amazon rainforest. The Amazon region is an essential part of the environment, which is a centre of biodiversity and contributes to the environment through carbon absorption. The deforestation problem that occurs in the Amazon region has a significant impact not only on Brazil but also globally. This is what underlies various international criticisms of Brazil, so it needs to be responded to diplomatically. By using qualitative methods and the concept of environmental diplomacy, this research finds that Brazil operates in four main strategies that represent the dynamics of environmental diplomacy practice. The strategy includes a commitment to achieving zero deforestation, holding meetings with Latin American countries to discuss the Amazon crisis, using the summit forum to negotiate with the United States in cooperation to overcome deforestation, and responding to trade demands from European countries that discriminate against Brazilian trade products. This response shows that basically Brazil is committed to realizing environmental preservation. However, there is a contradiction caused by Brazil's condition, which still needs to develop its economy amidst the current crisis. Therefore, the practice of environmental diplomacy is taken to become a momentum in raising awareness of the environment with the policies implemented by Brazil.